Innovative eco-friendly active packaging strategy aimed for ethylene removal - Rupérez Cebolla, David; Gracia Vallés, Nicolás; Nerín, Cristina; Silva, Filomena (Jornada de Jóvenes Investigadores del I3A, 2022)
Within the scope of sustainability, this work tackles both food waste and food safety by studying the ethylene scavenging potencial of α-cyclodextrin nanosponges produced by solvent-free synthesis and the food safety evaluation of the compostable packaging for food contact applications where the nanosponges will be incorporated.